The Inter-Asia Global Marriage: Interaksi Budaya di dalam Perkawinan Campuran Pasangan India-Indonesia di Jakarta - Angjaya, Song (Paradigma: Jurnal Kajian Budaya, 2014)
The paper analyzes the cultural interaction in mixed marriage of Indian national who live in Jakarta with Indonesian in the more penetrating globalization process in Asia in the 21st century. The research aims to examine the binding of two cultures tied in the knot in the marriage institution, its problem and negotiation. The qualitative methods used here is conducted through questionnaire and direct interview and through the social media. The result of which shows that factors such as cultural difference, respective country rules, and family tie interfere the social interaction in mixed marriage. But, despite the challenges, it is capable to generate negotiation and cultural appropriation of each party to support a multicultural and cosmopolitan marriage.